The Influence of The Power of Two Method in Mathematics Learning on Increasing Student Activity - Subandi; Prasetyo, Singgih Dwi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Mathematics learning aims to enhance problem-solving skills encompassing problem comprehension, method creation, execution, and result analysis. It covers numbers, geometry, calculations, and data processing. Low achievement in mathematics stems from inadequate understanding and reliance on arithmetic as a tool. Student disinterest further hampers learning. Although students may solve problems correctly, they often struggle to explain their reasoning, as observed in a class III student at SD Negeri 1 Pucangan. Student engagement is crucial in gauging learning motivation. Cooperative learning, particularly the power of two methods, fosters student collaboration, facilitating better comprehension. This approach enhances learning quality, promoting active and creative participation. Implementing the power of two cooperative learning models in class III at SD N 1 Pucangan improved student activity, shifting from adequate to good. The method's effectiveness in enhancing mathematics learning quality is evident through increased student engagement and activity levels